USING THE TECHNIQUES OF SCHEDULING THE PRODUCTION PROCESSES AND SUPPLY CHAIN MANAGEMENT IN THE FOGGY ENVIRONMENT; APPLIED RESEARCH OF THE ELECTRONIC PRODUCTION PLANT AT AL - ZAWRA GENERAL COMPANY – IRAQ - Abidalreda. N, Yosif; Al-Sammarraie B.Z, Hasan (International Journal of Supply Chain Management, 2019)
This paper gives an overview of the theory and practice of planning and scheduling in supply chains. For this purpose it seeks to solve the problem of loading the machines in the electronic production plant at Al-Zawra General Company, in the case of having more than one order at the same time, one of them within the overall plan (MPS), which in turn was the result of